Security System in the World - Sodikovich, Tursunov Kakhramon (Journal of Innovation in Education and Social Research, 2024)
The article examines the concept of security, its essence, perception, connection with other categories and the patterns that arise. The formation and evolution of the world's conceptual approaches to ensuring security are analyzed. And also special attention is paid to the main basic theories of international and regional security in modern political science.